Pengembangan Desa Wisata Berbasis Kearifan Lokal dan Ekonomi Kreatif: Pengabdian - M Alit Suryawan; Adi Artino; Abdul Rosid; Ramadhani Kirana Putra; Afni Yeni (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine efforts to develop tourism villages based on local wisdom and the creative economy. The implementation of activities is carried out through several stages, including preparation, data collection, program planning, activity implementation and mentoring, development and implementation, monitoring and evaluation, and dissemination of results and program sustainability. The results of this activity indicate that the program for developing tourism villages based on local wisdom and the creative economy has succeeded in increasing community capacity, strengthening institutions, and fostering village economic growth. Through training and mentoring, communities gain skills in tourism destination management, digital promotion, and creative economic production based on local potential. The formation of Pokdarwis and creative economy groups creates synergy in developing independent, inclusive, and competitive tourism. In addition to producing various tourism products based on local culture and crafts, this program also fosters a sense of togetherness, awareness of environmental conservation, and pride in cultural identity. The economic impact is seen in increased income, the creation of new jobs, and the growth of a sustainable local economy.